(untitled) (SCIENCE TIME JOURNAL, 2023)
This article explores the development of students’ ability to learn subjects in higher education institutions. It discusses various strategies and factors that contribute to subject mastery, including blended and online learning, student-led research and projects, mindfulness and well-being, gamification and interactive learning, adaptive feedback and coaching, global perspectives and international collaboration, social-emotional learning, continuous assessment and feedback, industry partnerships and internships, reflective portfolios and ePortfolios, peer collaboration and cooperative learning, experiential learning, the flipped classroom model, individualized learning plans, mentorship programs, critical thinking development, capstone projects, continuous professional development for instructors, peer tutoring and teaching assistantships, and data-driven decision making. By implementing these approaches, higher education institutions can create an environment that fosters active engagement, critical thinking, and a deep understanding of subjects, enabling students to master their chosen fields of study.